Analyzing inter-organization communication between customer and supplier of subsidized paddy fertilizer - Saad, M.S.M. (Canadian Center of Science and Education, 2015)
Inter-Organization Communication (IOC) is a commonly used communication discipline to communicate between and among organizations. This paper aimed to investigate elements of IOC theories of communication management used between a local farmer union (PPK) and subsidised fertilizer suppliers based on the perspectives of the PPK. This study employed a quantitative method through a survey using questionnaires which were distributed to a total of 192 representatives of 63 PPKs from granary areas. The findings revealed two essential indicators to support inter-organizational communication; communication willingness and communication commitment. This study will be useful for both scholars and practitioners in further understanding the current situation of communication in subsidized fertilizer industry in Malaysia. Further study on another variables in IOC and the relationship between components/variables involved would be beneficial on expanding knowledge of inter-organizational communication. Â© 2015, Canadian Center of Science and Education. All rights reserved.